Quality Assessment of Some Imported and Local Canned Tuna Sold in Kafrelsheikh, Egypt - Nagy, Nancy; Kirrella, Ghada A.K.; Moustafa, Nader Y.; Abdallah, Reda (Journal of Advanced Veterinary Research, 2023)
This study was conducted to evaluate and compare between some local and imported canned tuna products sold in supermarkets of Kafr El Sheikh Governorate, through physicochemical, bacteriological and sensory parameters assessment also, determining mercury and histamine level to ensure product safety. The results revealed that all examined tuna samples physiochemical parameters (pH, total volatile nitrogen (TVN), and thiobarbituric acid (TBA)) were compatible with the Egyptian specifications and considered safe for consumption. The microbial examinations indicated that samples show incidence of S. aureus was 44% for imported tuna. While for local chunk and shredded were 56% and 67%, respectively. In addition to detection of its enterotoxins, which were 11% and 22% for local chunk and shredded samples, respectively. The enterotoxins of isolated S. aureus were type A, detected from local chunk and types A, C, and D from local shredded samples. The incidence of anaerobic bacteria was 22% and 33% for local chunk and shredded samples, respectively, but not detected in imported samples with no detection of Clostridium perfringens in all local and imported samples. However, the imported and local samples were significantly different. All local tuna samples contained high level of mercury exceeded the permissible limits of 0.5 mg/kg while, the imported samples within the limit.Â Also, histamine levels were found within the Egyptian Standards of (20 mg/100 g) although there was a significant difference between imported and local samples. In conclusion, the results pointed out that all examined local and imported canned tuna samples agreed with the Egyptian and other standards making them considered safe for human consumption. Â